MENINGKATKAN KUALITAS REPEATABILITY DAN REPRODUCIBILITY SAMPEL LIQUID GAS DE-ETHANIZER DI PT. BADAK DENGAN MEMODIFIKASI ALAT PREPARASI PADA KROMATOGRAFI GAS - Ardiansyah -; Chairul Saleh; Rahmat Gunawan (JURNAL KIMIA MULAWARMAN, 2014)
Modification has been done to the gas chromatograph by adding a de-ethanizer preparation tool that serves as the evaporation of liquid samples de-ethanizer gas from the LNG (Liquid Natural Gas) plant PT. Badak NGL Bontang, East Kalimantan. With the aim to obtain stable analysis results as required. From the results obtained for the repeatability value 0.104% methane component, 0.036% ethane component and 0.154% propane components and reproducibility values obtained for the methane component of 0.025%, 0.036% component ethane, and propane components 0.014%. Data analysis of the samples obtained test results are still below thelimit allowed by the method of GPA 2261-64 which found samples with good homogeneity so that the analysis becomes stable and the true value can be resposibility and laboratory as a Quality Control can keep reliability for LNG Plant. Keywords: liquid natural gas, de-ethanizer, gas chromatography, repeatability, reproducibility, GPA2261-64